The impact of community service experience on self esteem among UiTM Pahang students / Hazlin Hasan … [et al.] - Hasan, Hazlin; Abu Bakar, Suwaibah; Solat, Naliza; Nikman, Khairunisa; Jais, Mohammad (2013)
Community service is motivated by the need to help others without waiting for anything in return. Those who have taken on community service projects have greatly benefited from their work, gained memorable experiences, and also built unique character traits. The importance of involving in community service activities among youths has been emphasized by the Malaysian Government through its Ministry of Education's eleven areas of reform which saw the community service component being added as part of the ministry's range of actions to inculcate students with core, universal value and strong Malaysian identity. It is believed that childhood experiences and up bringing form the basis on which one's self-esteem is built, but experiences in adulthood and how we deal with them also affect our self-esteem levels. Therefore, the main objective of this study is to determine the impact of community service experiences on self-esteem among UiTM Pahang students. A set of questionnaire was distributed to a cluster of Diploma of Office Management students who have organized community service projects for their Organizing Events (0MT290) course. The data were analyzed for descriptive and regression analysis using the SPSS Version 21. It is hoped that the findings would provide significant contributions to the areas of community service and character building of young people.